A study on the management of benign ulcers of leg and foot - R., Shivakumar C.; Ravindra, Chimkode (International Surgery Journal, 2016)
Background: Several factors contribute to the development of leg ulcers. However majority of ulcers are due to venous insufficiency which accounts for about 80-85% of all cases. Frequency of venous ulcers increases with age as a result of several factors such as immobility and venous disease. Methods: A descriptive study was carried out in Department of Surgery at a tertiary care hospital. Study subjects included 60 cases ulcers of leg and foot admitted to the Department of Surgery during the study period. Results: The most common procedure done in our study group for varicose ulcers to treat the primary cause was combined procedure of Stripping of the vein and hook phlebectomy in 55% followed by Hook phlebectomy alone in 36% and stripping alone in 9%. Conclusions: The treatment of the underlying cause is far more important than the choice of dressing.